Incidence of symptomatic venous thromboembolism after different elective or urgent surgical procedures - White, Richard H.; Zhou, Hong; Romano, Patrick S. (Thrombosis and Haemostasis, 2003)
There have been no comprehensive studies that have compared the incidence of symptomatic VTE over a spectrum of different urgent or elective surgical procedures. In this study we determined the incidence of symptomatic venous thromboembolic events (VTE) within a 3 month period after 76 different surgical procedures. Using a large administrative data-base, we analyzed 1,653,275 cases that underwent one of 76 selected surgical procedures between January 1, 1992 and September 30, 1996. The principal outcomes were venous thrombosis or pulmonary embolism, during either the initial hospitalization or a re-hospitalization for VTE within 91 days of the date of surgery. Predictors of VTE were analyzed using logistic regression. Overall, VTE was diagnosed in 13,533 cases (0.8%, 95% CI = 0.7-0.9%) and of these, 5049 (37%, 95% CI = 36-38%) had pulmonary embolism. Predictors of VTE included: advancing age (OR=1.1 per 5 year increment in age, 95% CI =1.1-1.1), Latino ethnicity (OR = 0.9, 95% CI =0.8-0.9), Asian/Pacific Islander ethnicity (OR = 0.5, 95% CI = 0.4-0.6), presence of a malignancy (OR = 1.7, 95% CI = 1.6-1.8) and prior VTE (OR = 6.2, 95% CI = 5.5-7.0). High-risk procedures that had an incidence of symptomatic VTE of approximately 2 to 3% included invasive neurosurgery, total hip arthroplasty, major vascular surgery and radical cystectomy. Fifty-six percent of all VTE events diagnosed within 91 days of surgery occurred after discharge. The findings of this study provide a basis for categorizing different surgical procedures as low, intermediate, high and very high risk for VTE. Because of the high incidence of VTE diagnosed after hospital discharge, further studies of extended thromboprophylaxis appear warranted.
Keywords: Thromboembolism; surgery; complications; venous thrombosis; epidemiology